2019
DOI: 10.1093/aobpla/plz019
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomics sheds light on differential adaptation and species diversification between two Melastoma species and their F1 hybrid

Abstract: Variation in gene expression promotes adaptive divergence. In this study, we performed comparative transcriptomics on Melastoma candidum , M. sanguineum and their F 1 hybrid to investigate the role of gene expression in plant species diversification and hybridization. Differentially expressed genes were mostly found between the two parental species, and were related to adaptive traits that limit the species to their habitats. In the F … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 79 publications
0
10
0
Order By: Relevance
“…The high-quality genome assembly of M. candidum makes it feasible to provide genomic insights into the evolution of trichomes, a key trait in contributing to species diversification and ecological adaptation in Melastoma (Wong, 2016;Ng et al, 2019;Huang et al unpublished data). Based on the remarkable trichome diversity in Melastoma, we predict the expansion of trichome-related genes in the M. candidum genome, which can provide the raw materials for trichome evolution and thus effective response to diverse biotic and abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high-quality genome assembly of M. candidum makes it feasible to provide genomic insights into the evolution of trichomes, a key trait in contributing to species diversification and ecological adaptation in Melastoma (Wong, 2016;Ng et al, 2019;Huang et al unpublished data). Based on the remarkable trichome diversity in Melastoma, we predict the expansion of trichome-related genes in the M. candidum genome, which can provide the raw materials for trichome evolution and thus effective response to diverse biotic and abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…It also plays an important role in biological functions such as development, seed dispersal, adaptation to extreme temperatures, and signal transmission (Hegebarth et al, 2016;Zhao and Chen, 2016;Zhou et al, 2017). Previous studies in Melastoma suggested that trichomes of different species or populations might contribute to their differential adaptation to heterogenous habitats (Ng et al, 2019). For example, M. candidum, always found in open habitats, has densely covered scales in the hypanthia and densely covered hairs in the leaves, which can resist the (UV) irradiation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Oftentimes strategies employed follow two main paths. On one hand, de novo approaches are often used because they allow to represent the genes of both parental species (eg., [6,69]) but the gene structure in introns and exons (for species for which a reference is available) is then lost on the way, along with the information about the species each genes is representative of, in addition chimeric transcripts can also be assembled. On the other hand, some studies chose to use the genome of one of the two parents to conserve genome structure information and ease analyses but oftentimes the mapping rate of the other species is lower, and the analysis of gene expression in hybrids is biased toward one of the parental species (eg., [5]).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that regulatory changes likely play a more important role than coding changes in closely related species of both animals and plants ( Jones et al, 2012 ; Ng et al, 2019 ). Lupa and BGE 016880 shared a high degree of similarity in their transcriptomes; however, gene expression levels in response to shade were quite different between them.…”
Section: Discussionmentioning
confidence: 99%